PERLINDUNGAN HUKUM HAK CIPTA TERHADAP SENIMAN ACEH DALAM INDUSTRI LAGU ATAU MUSIK ACEH BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Sofyan Jafar; Joelman Subaidi; Dedy Syahputra (Jurnal Geuthèë: Penelitian Multidisiplin, 2022)
In Indonesia, Copyright is regulated in Law Number 28 of 2014 concerning Copyright. One of these Copyright protections is songs or music, including the Copyright of Aceh songs or music which has experienced such rapid development, even now it has penetrated into the internet world. Therefore, this article is intended to examine and analyze the extent of knowledge of Acehnese artists, because there are still many Acehnese artists' works – especially in Acehnese music and songs – which are adapted and used by others without the permission of the copyright owner. The use of music and songs is indeed justified if it is done by asking permission from the copyright owner. This research is a qualitative legal research with a normative approach and is supported by empirical data using primary and secondary data. The results of the study found that there are still copyright infringement practices in the production of songs or music in Aceh, including the use of songs or music in Aceh that are used without permission from the copyright holder, such as singing songs or music by other people without permission which is then uploaded. on social media and internet media such as YouTube which is commonly known as Cover. This act clearly violates the rule of law and has ignored the moral and economic rights of the copyright owner.